2015
DOI: 10.1126/scitranslmed.aac5811
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced species divergence in corticospinal tract reorganization and functional recovery after lateralized spinal cord injury favors primates

Abstract: Experimental and clinical studies suggest that primate species exhibit greater recovery after lateralized compared to symmetrical spinal cord injuries. Although this observation has major implications for designing clinical trials and translational therapies, advantages in recovery of nonhuman primates over other species has not been shown statistically to date, nor have the associated repair mechanisms been identified. We monitored recovery in more than 400 quadriplegic patients and found that that functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 45 publications
6
119
1
1
Order By: Relevance
“…These studies suggested a relationship of PNs to recovery, but such lesion might affect other group of neurons besides PNs, and demonstration of causal contribution of PNs was still indirect. Furthermore, because there are considerable differences in neural structures and body apparatus related to hand movements between rodents and primates (12,36,37), studies in nonhuman primates are critical for translating therapeutic strategies to treat spinal cord injury in humans (38,39). Therefore, direct evidence to show the causal contribution of PNs to recovery in nonhuman primates was needed.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested a relationship of PNs to recovery, but such lesion might affect other group of neurons besides PNs, and demonstration of causal contribution of PNs was still indirect. Furthermore, because there are considerable differences in neural structures and body apparatus related to hand movements between rodents and primates (12,36,37), studies in nonhuman primates are critical for translating therapeutic strategies to treat spinal cord injury in humans (38,39). Therefore, direct evidence to show the causal contribution of PNs to recovery in nonhuman primates was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injury affects millions of people worldwide and typically has life-long consequences (Friedli et al, 2015). In the United States alone, ∼30 individuals sustain a spinal cord injury every day (Gomes-Osman et al, 2016), typically caused by motor vehicle accidents (38%), falls (>22%), violence (13.5%), and sports and recreational accidents (9%).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work (Friedli et al, 2015) highlights the utility and relevance of non-human primate clinical spinal cord injury models. Interestingly, these studies revealed significant interspecies differences in the mechanisms of corticospinal tract regeneration during motor recovery when comparing rodents to primates and humans.…”
Section: Discussionmentioning
confidence: 99%